2013
DOI: 10.5026/jgeography.122.591
|View full text |Cite
|
Sign up to set email alerts
|

Geomorphic Dynamics and Sediment Budget in the Southern Japanese Alps: Recent Studies and Prospects

Abstract: This review paper synthesizes geomorphic dynamics, sediment transport and resulting natural hazards in mountains of the southern Japanese Alps and their drainage basins, where climatic and geological situations produce highly active landform dynamics. In alpine areas above the timber line, shallow diurnal freeze-thaw action operating in the thin topsoil produces smallscale periglacial forms, and gravitational spreading leads to numerous sackung features where snow-melt and heavy rain in places promote rockslid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…These findings suggest that clear terrace components of our study are common for V-shaped valleys in mountainous regions, irrespective of the climatic zone; besides, terrace segments were more conspicuous, which was caused by scarps of terraces being detectable as clear units. Rocky debris assumed to have been supplied by infrequent deep-seated landslides as noted to be relevant to Minami Alps geology (Matsuoka et al 2013) may reinforce this morphological attribute. Tsukamoto (1998) also remarked on the contribution of debris flow to the emergence of terrace segments in mountain valleys.…”
Section: Micro-landform Structurementioning
confidence: 72%
See 2 more Smart Citations
“…These findings suggest that clear terrace components of our study are common for V-shaped valleys in mountainous regions, irrespective of the climatic zone; besides, terrace segments were more conspicuous, which was caused by scarps of terraces being detectable as clear units. Rocky debris assumed to have been supplied by infrequent deep-seated landslides as noted to be relevant to Minami Alps geology (Matsuoka et al 2013) may reinforce this morphological attribute. Tsukamoto (1998) also remarked on the contribution of debris flow to the emergence of terrace segments in mountain valleys.…”
Section: Micro-landform Structurementioning
confidence: 72%
“…Because of the geological conditions and abundant rainfall, deep valleys have developed. Deep-seated large landslides adding shallow and rapid slope failures frequently occur as one of the most active mass-movement areas in Japan (MLIT Japan 2012b; Matsuoka et al 2013). Basements of valleys are sometimes covered with thick deposits originating from the deep-seated landslides (Matsuoka et al 2013); however, exposed bedrock is continuously observed in this study site, namely, bedrock in 60-90% of the total length of the stream segments studied, indicating a "bedrock channel", a major type of topographical feature for mountain streams (Tsukamoto 1998).…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the upper hypogean zone, in which T. kuznetsovi adults live, is a few or some dozen centimeters below the slope surface of a v-shaped valley. Trechiama kuznetsovi adults would occasionally be exposed to the surface due to landslides occurring as a result of precipitation or earthquakes [48][49][50]. This temporary light stimulus could function as a selective pressure to retain the function of opsin genes and other phototransduction genes.…”
Section: Discussionmentioning
confidence: 99%